Use of Magill Forceps to Remove Foreign Bodies in Children - Oncel, Murat; Sunam, Guven Sadi; Elsurer, Cagdas; Yildiran, Huseyin (The Surgery Journal, 2017)
Introduction Esophageal foreign body (FB) in all age groups can cause serious morbidity or mortality. The study aims to report our experience retrieving FBs from the upper esophagus in children using Magill forceps. Materials and Methods In this study, 88 patients (45 males [51.1%] and 43 females [48.9%]) were presented with suspected FB ingestion. FB ingestion was determined via endoscopic analysis, or lateral and posterior–anterior radiographies, including oropharynx, neck, chest, and abdomen. Cases were classified into seven groups, according to history, diagnostic method, and postintervention findings, as follows: (1) coins, (2) toys, (3) metals, (4) bones, (5) battery, (6) glass, and (7) food. A laryngoscope was used to elevate the larynx and expose the esophageal entrance. Magill forceps were advanced into the esophagus and opened to observe and extract the FB.Results All 88 patients who underwent endoscopic examination due to suspected FB ingestion were confirmed to have ingested a FB. Median age was 12 years; 15 patients were aged < 5 years; 63 (71.5%) were diagnosed based on routine radiographic findings, and others were diagnosed based on physical findings and history. The most common type of FB was coins (n = 51 [57.9%]). Mean surgical duration was 20 minutes.Conclusion FBs located at cervical esophageal level are usually the most difficult to remove. Magill forceps should be used before other methods.
Keywords: Magill forceps; foreign bodies; methods